PENGARUH MEDIA DASAR DAN ZAT PENGATUR TUMBUH BAP PADA PERBANYAKAN MIKRO Pinus merkusii - ILG Nurtjahjaningsih (Jurnal Pemuliaan Tanaman Hutan, 2009)
Micropropagation technique is applied to produce large number of plants. Juvenile explants and culture medium are two crucial factors that influence the success.The aims of this study were to determine culture medium that was effective to induce shoot and to produce plantlests from embryo culture of Pinus merkusii. Screening of five cytokines and five basal medium were carried aut. Then, explants wee cultured on the best cytokine and basal medium for plant regeneration. The results showed that BAP was the best cytokine type; LP and GD medium were the best medium compositions for shoots induction. GD medium supplemented by high consentration BAP showed the best medium for shoots induction. Solid GD medium containing 0,25uM BAO was effective for multiple shoots. Liquid GD medium without plant hormone was the best composition for shoots elongation. Half strength of GD medium without plan hormone gave the best result for rooting.